Optimización básica del rodete de una bomba centrífuga de 500 Watios mediante dinámica de fluidos computacional (CFD). - Castillo Amézquita, Jorge Armando (Universidad Antonio Nariño, 2021)
The general objective of this project is to evaluate the geometry of the impeller of the 500- watt centrífugal pump of the Antonio Nariño University, Tunja headquarters (UAN) by using the CAD tool (Autodesk Inventur) with the simulation and development of a computational analysis. of fluids (CFD) in order to optimize its performance, since a drop in the pressure head and a decrease in the flow provided by the pump can be observed.